Water, Human Rights, and Economic Instruments the Islamic Perspective (Water Nepal, 2003)
The countries of Middle East and North African (MENA) region have one of the highest average population growth rates in the world as well as scarce natural water supplies. This paper looks at the challenges of water management in the region by exploring various conceptual strands that have evolved in the discourses around water from an Islamic perspective. Islamic percepts allow the functioning of free and fair markets for water but governments need to intervene if the principles of equity and public interest are being contravened.Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.197-214